MODELING INDONESIA'S FOOD SECURITY INDEX USING SPATIAL ECONOMETRIC PANEL APPROACH - Amelia, Dita; Suliyanto, Suliyanto; Aldawiyah, Najwa Khoir; Zhafira, Azizah Atsariyyah (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Food security is a pressing issue for economic stability and public well-being in Indonesia, where the 2020–2022 Food Security Index (FSI) remained at Priority 4 which indicate low provincial food security. This study examines the determinants of FSI across 34 provinces from 2020 to 2023 using a spatial panel approach to capture both temporal and spatial spillovers. Secondary data from the National Food Agency and the Central Statistics Agency (BPS) include poverty rate, electricity and clean water access, Desirable Dietary Pattern (DDP) score, per capita caloric intake, and mean years of schooling. Analysis employed panel regression and spatial-panel models particularly corporating the spatial fixed effects model. The SAR-FE model provided the best fit, with a significant positive spatiall ag coefficient. This study emphasizes that FSI in one province is influenced by neighboring provinces. These spillover effects highlight the interconnectedness of provincial food security and emphasizing that interventions in one region can affect adjacent areas. The combination of spatial and panel methodologies with individual fixed effects defines the novelty of this research. Such an approach, which is rarely utilized in the context of Indonesian food security, uncovers provincial-level spillover dynamics that previous studies relying solely on either spatial or panel frameworks tended to ignore. Findings provide actionable insights for coordinated regional policies and contribute to Sustainable Development Goal 2 (Zero Hunger) by promoting more equitable food availability and accessibility.